The Hudson’s Bay Company as a Context for Science in the Columbia Department - Schefke, Brian (Scientia Canadensis, 2008)
AbstractThis article aims to elucidate and analyze the links between science, specifically natural history, and the imperialist project in what is now the northwestern United States and western Canada. Imperialism in this region found its expression through institutions such as the Hudson’s Bay Company (HBC). I examine the activities of naturalists such as David Douglas and William Tolmie Fraser in the context of the fur trade in the Columbia Department. Here I show how natural history aided Britain in achieving its economic and political goals in the region. The key to this interpretation is to extend the role of the HBC as an imperial factor to encompass its role as a patron for natural history. This gives a better understanding of the ways in which imperialism—construed as mercantile, rather than military—delineated research priorities and activities of the naturalists who worked in the Columbia Department.